STUDENTS’ SCORE IMPROVEMENT ON WRITING DESCRIPTIVE TEXTS - Setiawati Setiawati; Tahrun Tahrun; Artanti Puspita Sari (ELTE Journal (English Languange Teaching and Education), 2020)
This article is concerned with the inquiry on the influence of interactive multimedia and reading habit toward students’ writing achievement. This study is aimed to investigate the empirical evidence about interactive multimedia and reading habit and its influence on writing achievement. The population of this study encompassed all the seventh-grade students of Ar Rahman Islamic Junior High School of which total is 112 students. From the population, only 34 students were taken as samples. A simple random sampling technique was used in recruiting the samples. This is a quantitative study. The data were collected by using questionnaire, pre-test, and post-test. Data were analyzed by using t-test and Two Way Anova. Findings show that there were significant influences of interactive multimedia and reading habit toward seventh-grade students’ writing achievement. There were interaction effects from the application of interactive multimedia and reading habit on the seventh-grade students’ writing achievement. There was a significant difference in writing achievement between seventh-grade students who had high reading habits and those who had low reading habits taught by interactive multimedia. The conclusion suggests that interactive multimedia and reading habit show significant roles to improve students’ writing achievement of descriptive texts.